Spanish Cultural Diplomacy Toward France Throught El Programa Para la Internacionalización de la Cultura Española (PICE) - Fuat Albayumi, Fuat Albayumi; Awani Rahmadillah, Cahya Awani Rahmadillah; Sugiarto Pramono, Sugiarto; Muhammad Iqbal, Muhammad Iqbal (Rumah Jurnal, University of Jember, 2025)
Culture is one of the soft power instruments for building good relationships between countries. The Spanish government has carried out cultural diplomacy through the El Programa Para la Internacionalización de la Cultura Española (PICE) since 2013, with France as one of the target countries for implementation. As a country with a diverse culture, Spain uses it as an instrument of diplomacy. Nevertheless, PICE as a cultural diplomacy program has obstacles to global implementation. France as a country that is geographically directly adjacent and as one of the potential markets for Spanish cultural tourism. This study aims to learn about the implementation of a cultural diplomacy strategy toward France through PICE. This study uses a qualitative descriptive research approach with a literature study as the data sources. Using the concept of public diplomacy and cultural diplomacy, it was found that the PICE program toward France in the first 10 years was implemented through 4 cultural activities, artist mobility, cultural exchange, cultural representation, and collaboration with France cultural institutions. Thus, PICE toward France became a tool for giving a broader perspective about Spain to the France public through the cultural instrument and also strengthened the existing bilateral relations between Spain and France.